Promoting positive youth development and well-being in comprehensive transition programs for court-involved youth - Gore, Taryn (2018)
The purpose of this study was to gain a deeper understanding of how community-based organizations are supporting the positive development of court-involved youth. More specifically, this study examined how organizations support youth’s access to work-based learning opportunities. This study also investigated how organizations determine the kinds of activities to implement in their comprehensive transition programs. Additionally, this study sought to understand whether and in what ways these programs are incorporating positive youth development (PYD) principles. Purposive sampling identified five organizations that are implementing work-based learning programs for court-involved youth. These organizations were located in the Midwest, South, East and Western regions of the United States. The research considered multiple sources of data, including documentation review, semi-structured interviews, field notes and survey interviews. Documents collected included administrative reports, brochures, evaluation reports, annual reports, samples of recruitment materials, youth needs assessment, and partnership agreements with businesses. The semi-structured, open-ended interview was conducted with an executive director of each organization using an interview protocol that was guided by positive youth development and well-being frameworks. Survey interviews were conducted with other stakeholders of the organizations using a structured qualitative questionnaire. The data were analyzed using cross-case analysis. Each organization’s documentation, survey data and interviews were studied as a separate case to identify similarities, differences and unique patterns within the data. Then, a logic model was generated for each organization. Next, the separate logic models were compared using cross-case analysis. Lastly, based on the knowledge that emerged from the analyses, a proposed theory of change was created illustrating potential ways to incorporate positive youth development to guide future program design efforts. The major findings of the study were: (1) partnerships with various organizations explain the extent to which court-involved youth gain access to WBL activities; (2) the development of a theory of change, framework or assumptions based in evidenced based research impacts the integration of PYD principles in program activities; and (3) implementation of PYD principles varies across organizations